What Kerdoe's Vegetative Index really reflects? - Oleksandra I. Fajda; Borys V. Hrinchenko; Oleh V. Snihur; Liliya G. Barylyak; Walery Zukow (Kazimierz Wielki University, 2015)
Fajda Oleksandra I., Hrinchenko Borys V., Snihur Oleh V., Barylyak Liliya G., Zukow Walery. What Kerdoe's Vegetative Index really reflects? Journal of Education, Health and Sport. 2015;5(12):279-288. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35421 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A279-288 http://pbn.nauka.gov.pl/works/681547 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015.   WHAT KERDOE'S VEGETATIVE INDEX REALLY REFLECTS?   Oleksandra I. Fajda1, Borys V. Hrinchenko1, Oleh V. Snihur1, Liliya G. Barylyak2,3, Walery Zukow4   1JSC "Dnipro-Beskyd", Truskavets', Ukraine    alexavka7@gmail.com; verdo 2JSC " Truskavets'kurort", Truskavets', Ukraine 3Laboratory of Experimental Balneology, OO Bohomolets' Institute of Physiology NAS, Truskavets'-Kyiv     i.popovych@ukr.net 4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   w.zukow@ukw.edu.pl   Abstracts   Background. Index I Kerdö, the author proposed back in 1966, ie before the era HRV, to quantify the autonomic tone continues to be widely used. We set a goal to analyze the relationships Kerdö's Vegetative Index (KVI) with parameters of HRV and EEG, as well as with Mineralocorticoide, Calcitonin and Parathyrin Activities. Methods. In basal conditions in men, patients with chronic pyelonephritis and cholecystitis in remission, recorded Blood Pressure and Heart Rate ("Omron-4MI", Netherland), HRV ("Cardiolab+VSR", KhAI Medica, Ukraine) and EEG ("NeuroCom Standard", KhAI Medica, Ukraine). In urine determining the concentration of Phosphates, Calcium, Potassium and Sodium. Results. No correlation ascertained between KVI and LF/HF Ratio (r=-0,18) and Baevskiy's Vegetative Index (r=0,17). However, KVI weakly correlated with Power Spectrum Density (PSD) LF (r=-0,35), (VLF+LF)/HF Ratio (r=-0,32) and Baevskiy's Stress Index (r=0,32) as well as with Parathytin Activity (r=0,33), estimated by Urina Phosphates/Calcium Ratio. Medium strength correlation (r=0,56) found between KVI and Baevskiy's Activity Regulatory Systems Index in Orthostase. However, the strongest correlations of KVI proved with Amplitude of α-Rhythm Ongoiging EEG (r=0,57) and PSD P4-α (r=0,65). Canonical correlation between KVI, on the one hand, and the parameters of EEG, HRV and Parathyrin Activity, on the other hand, was very strong: R=0,933; R2=0,870; Adjusted R2=0,758; F(18)=7,8; χ2(18)=62; p<10-5. Conclusion. Kerdö's Vegetative Index reflects above all Amplitude of α-Rhythm EEG and its Power Spectrum Density in Parietal and Central loci, less options HRV, but is not marker of sympatho-vagal balance.   Keywords: Kerdö's Vegetative Index, HRV, EEG, correlations.